Correlation between cane growth and flowering behavior of Dendrobium orchid cultivars - Islam, MS; Mehraj, H; Roni, MZK; Shimasaki, K; Uddin, AFM Jamal (Journal of Bangladesh Academy of Sciences, 2014)
The experiment was conducted to observe the correlation of cane growth with floral behavior of nine Dendrobium cultivars. Results revealed that, cane growth of different Dendrobium cultivars influenced flowering behavior. The present experimental findings may help to determine standard cane growth for efficient nutrient management and commercial grade flower production of Dendrobium cultivars. DOI: http://dx.doi.org/10.3329/jbas.v37i2.17561 Journal of Bangladesh Academy of Sciences, Vol. 37, No. 2, 205-209, 2013